2016
DOI: 10.5966/sctm.2015-0131
|View full text |Cite
|
Sign up to set email alerts
|

Alginate-Encapsulation for the Improved Hypothermic Preservation of Human Adipose-Derived Stem Cells

Abstract: Despite considerable progress within the cell therapy industry, unmet bioprocessing and logistical challenges associated with the storage and distribution of cells between sites of manufacture and the clinic exist. We examined whether hypothermic (4°C-23°C) preservation of human adipose-derived stem cells could be improved through their encapsulation in 1.2% calcium alginate. Alginate encapsulation improved the recovery of viable cells after 72 hours of storage. Viable cell recovery was highly temperaturedepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 48 publications
(62 reference statements)
1
60
0
1
Order By: Relevance
“…Isotype controls were performed with antibodies against IgG. In addition, the adipogenic, osteogenic, and chondrogenic differentiation ability of the naive and transfected ASCs was determined as previously described 32,33 .…”
Section: Mir-150 Transfection Into Ascsmentioning
confidence: 99%
“…Isotype controls were performed with antibodies against IgG. In addition, the adipogenic, osteogenic, and chondrogenic differentiation ability of the naive and transfected ASCs was determined as previously described 32,33 .…”
Section: Mir-150 Transfection Into Ascsmentioning
confidence: 99%
“…Due to the fact that no ice forms during the process, the effects of cooling are often reversible. Hypothermia can be also used for short-term cell preservation on the order of hours to days [1921]. However, long-term preservation of cells has not been achieved using this approach.…”
Section: Cell Preservation Fundamentalsmentioning
confidence: 99%
“…Cell viability post-preservation was found to be 80% and 74% for the hMSCs and mESCs respectively [47]. Similarly, Swioklo et al (2016) showed human adipose-derived stem cells could be encapsulated and stored at a range of temperatures, from 4-23C, although 15C was found to be the optimal [48]. The disadvantage to this method however is the need for a cell retrieval step which increases process complexity and will likely need to be undertaken at-or nearclinic.…”
Section: Hypothermic Storagementioning
confidence: 99%